Making use of what teachers know and can do: Policy, practice, and national board certification. - Koppich, Julia E.; Humphrey, Daniel C.; Hough, Heather J. (Education Policy Analysis Archives, 2007)
This paper is the culmination of a three-year study that sought to frame an initial answer to the question, "What are the circumstances and conditions under which National Board Certified teachers (NBCTs) can have a positive impact on low-performing schools?" The study, funded by Atlantic Philanthropies, was part of the National Board's more comprehensive effort to answer a number of research questions about the impacts of board certification and board certified teachers in schools and districts across the country.